CNBP modulates the transcription of Wnt signalling pathway components - Margarit, Ezequiel (2014)
Background: Cellular nucleic acid binding protein (CNBP) is a small and highly conserved protein with nucleic acid chaperone activity that binds single-stranded nucleic acids. Data collected so far suggests that CNBP is required for proper craniofacial development. Despite the advances achieved in the last decade, the identity of the molecular targets of CNBP responsible for its role in rostral head development remains elusive. Methods: In this work we used the CNBP single-stranded DNA-consensus binding sequence to find out putative CNBP target genes present in the human, mouse, chicken, Xenopus and zebrafish genomes. Results: Most of the identified genes are associated with embryonic developmental processes, being three of them (cdk14, ptk7 and tcf7l2) members of the Wnt signaling pathway. This finding, along with previous one showing that CNBP down-regulates the transcription of Wnt5, aimed our work to address the role of CNBP on the WNT signaling players and pathway regulation. Experiments carried out in zebrafish developing embryos revealed that craniofacial morphology was more adversely affected as CNBP abundance decreased. Furthermore, we observed that CNBP up-regulated in a dose-dependent fashion the transcription of cdk14, ptk7 and tcf7l2, which in turn was reflected in c-myc, ccnd1 and axin2 expression. Conclusions: Results reveal a role of CNBP in transcriptional control of components of the Wnt signaling pathway, which might explain its requirement for proper craniofacial development.